Eosin Y Covalently Modified on Graphene Oxide for Enhanced Photocatalytic Activity toward the Degradation of Antibiotic Cefaclor under Visible Light Irradiation. Issue 8 (22nd February 2021) - Luo, Yue; Chang, Guorui; Huang, Li; Zhang, Leilei; Cui, Jiaqi; Zhu, Xiaping; Xu, Shuxia
Abstract: The covalent immobilization of eosin Y (EY) on graphene oxide (GO) was prepared and the obtained GO/EY composite can be used as a visible‐light‐driven photo‐catalyst for the degradation of cefaclor (CEC) antibiotics. The GO/EY composite exhibited much higher photocatalytic activity than pure GO and EY adsorbed GO. Using 2 mg L −1 of CEC at pH=7, 97 % degradation toward CEC could be achieved after irradiation time of 45 min. The enhanced photocatalytic activity for GO/EY composite can be attributed to the modification of GO by EY, which acted as a sensitizer for enhancing visible light absorption. The affecting factors of photocatalytic activities on the photocatalytic degradation of CEC were evaluated, including the effects of pH values, the photosensitized oxidation conditions and the reusability of the photocatalyst. Furthermore, the enhanced photocatalytic mechanism induced by visible‐light responsive GO/EY composite was proposed by reactive specie trapping experiments, and 1 O2 and H2 O2 were determined to be the main reactive oxygen species in the photocatalytic system. All these results demonstrated that organic dye sensitizer functionalized GO provided a nice candidate as a photocatalyst for the removal of CEC antibiotic from water under visible light irradiation. Abstract : Graphene oxide/eosin Y (GO/EY) composites were prepared by loading EY onto GO by covalent bonding, and were used to photocatalytic degradation of cefaclor under visible light.